1999
DOI: 10.1523/jneurosci.19-22-10082.1999
|View full text |Cite
|
Sign up to set email alerts
|

Total Number and Ratio of Excitatory and Inhibitory Synapses Converging onto Single Interneurons of Different Types in the CA1 Area of the Rat Hippocampus

Abstract: The least known aspect of the functional architecture of hippocampal microcircuits is the quantitative distribution of synaptic inputs of identified cell classes. The complete dendritic trees of functionally distinct interneuron types containing parvalbumin (PV), calbindin D(28k) (CB), or calretinin (CR) were reconstructed at the light microscopic level to describe their geometry, total length, and laminar distribution. Serial electron microscopic reconstruction and postembedding GABA immunostaining was then u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
371
4
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 440 publications
(410 citation statements)
references
References 42 publications
29
371
4
6
Order By: Relevance
“…In the dentate hilus of epileptic patients with hippocampal sclerosis, most of the few surviving hilar neurons are CB-IR [39] . Studies have indicated that the density of inputs and the total number of afferent synapses are several times higher on PV cells than on CB or CR cells, whereas the ratio of inhibitory inputs is significantly higher on CB and CR cells [40] , suggesting that PV-positive neurons receive more excitatory inputs than CB-and CR-positive neurons and thus are more vulnerable to excitotoxic damage. The AMPA receptor subunit GluR3 in PV-containing interneurons is highly expressed in the hippocampus and neocortex, whereas GluR2 is not observed, indicating that this is likely to contribute to the selective vulnerability of these interneurons to excitotoxicity [41] .…”
Section: Pv-immunoreactive (Pv-ir) Interneurons Arementioning
confidence: 99%
“…In the dentate hilus of epileptic patients with hippocampal sclerosis, most of the few surviving hilar neurons are CB-IR [39] . Studies have indicated that the density of inputs and the total number of afferent synapses are several times higher on PV cells than on CB or CR cells, whereas the ratio of inhibitory inputs is significantly higher on CB and CR cells [40] , suggesting that PV-positive neurons receive more excitatory inputs than CB-and CR-positive neurons and thus are more vulnerable to excitotoxic damage. The AMPA receptor subunit GluR3 in PV-containing interneurons is highly expressed in the hippocampus and neocortex, whereas GluR2 is not observed, indicating that this is likely to contribute to the selective vulnerability of these interneurons to excitotoxicity [41] .…”
Section: Pv-immunoreactive (Pv-ir) Interneurons Arementioning
confidence: 99%
“…Although individual afferent fibers had little effect on membrane potential for either AMPARs or KARs in our model, interneurons receive input from 1000 to 10,000 afferent fibers (Gulyas et al, 1999). To examine the effects of synaptically driven AMPARs and KARs when multiple fibers are active, we considered a model in which a small population of 50 fibers was activated.…”
Section: Ampar-and Kar-mediated Depolarization Driven By Multiple Fibersmentioning
confidence: 99%
“…Gamma oscillations are exquisitely susceptible to modulation of the cellular and synaptic mechanisms underlying the rhythmic activity. Fast-spiking PV+ interneurons are the main recipient of recurrent glutamatergic innervations in the hippocampal circuitry, and their role in gamma-frequency synchronization in cortical and hippocampal networks is well-established (34,35). Despite extensive knowledge of the role of BDNF-TrkB signaling in neuronal development and synaptic function, the question of how BDNF might modulate and control rhythmic activity has so far not been answered.…”
mentioning
confidence: 99%